2013
DOI: 10.1172/jci68760
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor microRNA FISH effectively differentiates tumor types

Abstract: MicroRNAs (miRNAs) are excellent tumor biomarkers because of their cell-type specificity and abundance. However, many miRNA detection methods, such as real-time PCR, obliterate valuable visuospatial information in tissue samples. To enable miRNA visualization in formalin-fixed paraffin-embedded (FFPE) tissues, we developed multicolor miRNA FISH. As a proof of concept, we used this method to differentiate two skin tumors, basal cell carcinoma (BCC) and Merkel cell carcinoma (MCC), with overlapping histologic fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
117
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(118 citation statements)
references
References 30 publications
1
117
0
Order By: Relevance
“…There is a trade-off between these parameters. The fixation of mouse sectioned tissues with EDC is initially carried out by incubation at 25°C (Pena et al 2009), which is subsequently increased to 50°C to achieve near-complete phosphoramide bond formation in a shorter time (Renwick et al 2013). Cross-linking of miRNAs with EDC for Northern blotting also shows that increasing the reaction temperature up to 60°C improves miRNA detection (Pall et al 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a trade-off between these parameters. The fixation of mouse sectioned tissues with EDC is initially carried out by incubation at 25°C (Pena et al 2009), which is subsequently increased to 50°C to achieve near-complete phosphoramide bond formation in a shorter time (Renwick et al 2013). Cross-linking of miRNAs with EDC for Northern blotting also shows that increasing the reaction temperature up to 60°C improves miRNA detection (Pall et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…More cross-linking at higher temperatures must lead to more retention of miRNAs, leading to stronger hybridization signals. However, cross-linking with EDC acts not only on miRNAs but also on proteins to form peptide bonds, which make the proteins resistant to proteinase (Sung et al 2003;Renwick et al 2013). As the surfaces of C. elegans larvae and adults are overlaid with cuticle layers composed of collagens, the layers have to be partially digested by proteinase so that WISH reagents, such as probes, can penetrate inward.…”
Section: Resultsmentioning
confidence: 99%
“…While several sequences including miR-375, miR-7, and miR-184 appear to be enriched in the endocrine pancreas, profiling results from mouse and human tissues have shown that none of these miRNAs are entirely specific to the islet [7] [8]. In the case of miR-375, expression of this miRNA has been reported in numerous tissue types including the pituitary gland, adrenal gland, intestine, lung, and several types of cancer [9] [10]. Similarly, miR-7 and miR-184 have been shown to be highly enriched in the central nervous system and eye, respectively [11].…”
Section: Microrna Profiling In the Pancreatic β-Cell And Isletsmentioning
confidence: 99%
“…In this issue of the JCI, Renwick et al (20) report on a method for detection and measurement of microRNAs in clinical samples (20). This work represents a significant technical advance in the development of a reliable, clinical laboratory-compatible RNA FISH methodology for molecular diagnostic applications.…”
Section: Research Advancesmentioning
confidence: 99%
“…A notable limitation of the study is that the RNA FISH-based methodology was conclusively validated only for two tumor-specific miRNAs (miR-205 and miR-375) in the small number of clinical samples analyzed to date. In the context of the expressed commitment of this group to explore the clinical utility of RNA FISH-based microRNA analyses in larger collections of clinical samples (20), this study has significant translational implications, because altered expression and activity of miR-205 and miR-375 has been linked to the increased likelihood of developing castration-resistant phenotype of human prostate cancer (13).…”
Section: Research Advancesmentioning
confidence: 99%